Perceptions of People Towards Youth with Autism Spectrum Disorder and Intellectual Disability in North Eastern Nigeria - M. Abdullahi , Abubakar,; T. Darma , Abdulkadir, (Kashere Journal of Education, 2021)
This paper examined people’s perception towards youth with Autism spectrum disorder (ASD) and intellectual disability. In-depth interviews were conducted separately with a with autism spectrum disorder (ASD) and intellectual disabilities (ID) While their mothers were thoroughly investigated in order to ascertain the level of victimisation in the form of bullying, these categories of youth constructs from the interview were utilised to compare groups on the frequency type and impact of victimization. The outcomes of the interview conducted reveals that youth with ASD are being victimised more frequently than their ID peers and that the form of bullying being subdued differs from each group to another. In view of submission our findings show that higher internalising problems and conflicts in relationship are found to be a significant predictor of victimisation. The paper, therefore, recommends among others that observation of extrinsic and intrinsic behaviours for proper adjustment in a classroom setting should be taken care off.